Influencing factors and behavior mechanism of the initial coulombic efficiency of silicon/graphite composites in lithium-ion batteries. (10th January 2021) - Gu, Zhiqiang; Li, Wenli; Miao, Yu; Chen, Yuxi; Xia, Xiaohong; Chen, Gairong; Liu, Hongbo
Highlights: Four types of Si/G composites with the same components and different combination ways are prepared by simple methods. Four types of Si/G composites are prepared to study the internal factors affecting the initial coulombic efficiency. The Si-G@C with large specific surface area still owns the highest initial coulombic efficiency. Abstract: Investigating the internal factors that affect the initial coulombic efficiency (ICE) of silicon/graphite (Si/G) composites and improving ICE are critical to promote applications of Si/G composites in lithium-ion batteries. Here, four types of Si/G composites are prepared with different specific surface area, Si–G phase interface and charge transfer impedance ( R ct ) to study the internal factors affecting the ICE of Si/G composites. The experimental results show that the influencing factors on ICE of Si/G composites are not only specific surface area, but also the Si–G phase interface and R ct . During the first lithiation process of Si/G composites, there are some reversible phase (Li x Si, Li x C) and irreversible phase (Li2 O, Li2 SiO4 and organolithium) formed, the ICE of Si/G composites is mainly determined by the irreversible phase. The specific surface area, R ct and Si–G phase interface can affect the reaction kinetics of the materials and the ratio of reversible/irreversible phase content, which ultimately affect the ICE of Si/G composites. A smaller specific surface area and well Si–G phase interface with a low R ct will bring a higher ICE of Si/G composites. This report may provide a new idea for the research of ICE of Si/G composites and promote their practical application. Graphical abstract: The Si–G, Si–G@C, Si@C–G and Si@C–G@C composites are prepared with different specific surface area, Si–G phase interface and charge transfer impedance ( R ct ) to study the internal factors affecting the ICE of silicon/graphite composites. The Si–G@C with large specific surface area still owns the highest ICE, due to the well Si–G phase interface and a low R ct, which can affect the reaction kinetics to generate more reversible phase (Li x Si, Li x C) and less irreversible phase (Li2 O, Li2 SiO4 and organolithium). Image, graphical abstract